Crisis management strategies in economic Institutions - براهم نور الهناء; بوجدار الهام; الياس الهاني فراح (Finance and Business Economies Review, 2019)
The study aimed to clarifying the importance of implementing crisis management strategies in economic institutions, reviewing the most important concepts related to crises, and how to confront crises through the implementation of the concept of crisis management. Among The results, we noted that the mission of the institution does not finiched when facing crises, but extends to good implementation and effective monitoring of crisis management, and adopting an effective strategic approach that makes it more vital in an environment full of opportunities. Crisis strategies vary depending on the type and magnitude of the crisis facing the institution. The study reached a number of recommendations, us the good preparation of programs and plans for crisis management in institutions and working on their review development continuonsly. While promoting the interest of businesses, have sufficient knowledge to use crisis strategies in ordre to acquire the ability to meet and overcome sudden crises efficiently and effectively.